PENGARUH MEDIA V POCKET DAN POSTER UNTUK MENINGKATKAN PENGETAHUAN TENTANG ASUPAN FE SEBAGAI BENTUK PENCEGAHAN ANEMIA PADA KELOMPOK REMAJA PUTRI VEGETARIAN DI INDONESIA VEGETARIAN SOCIETY (IVS) JAKARTA - Ayu Wulandari (2021)
The main cause of iron deficiency anemia is due to insufficient intake of Fe (iron). If a person consumes less iron and insufficient iron storage in the body, this can lead to the risk of iron deficiency anemia. What can be done is to increase knowledge about iron intake and anemia as well as efforts to prevent anemia through various media. One of the media that can be used is poster media and V Pocket Application media. The purpose of this study was to determine the effect of "V Pocket" application media and posters to increase knowledge about iron intake and anemia and the level of anemia prevention efforts in a group of young vegetarian girls in the Indonesian Vegetarian Society (IVS) Jakarta. This study used purposive sampling technique with a sample of 70 respondents. The research method used experimental with pre-post test two group design with Wilcoxon test to determine the difference before and after and Mann-Whitney test to see the effectiveness of the media. The results showed that treatment with V Pocket application media was more effective in increasing knowledge of anemia and iron intake and anemia prevention efforts compared to poster media. Suggestions for further research to use application media and emphasize more material about food ingredients that stagnate and help the absorption of Fe.